Observational study of first-line chemotherapy including cetuximab in patients with metastatic colorectal cancer: CORAL trial - Muro, Kei (Jpn J Clin Oncol, 2019)
OBJECTIVE: We aimed to clarify the clinical practice and outcomes of first-line cetuximab-containing chemotherapy in patients with metastatic colorectal cancer. Efficacy and safety were evaluated in each group classified by the European Society for Medical Oncology Guidelines 2012. METHODS: This prospective observational study included patients with previously untreated metastatic colorectal cancer from 158 centers in Japan who started first-line cetuximab-containing chemotherapy from January 2012 to June 2013 and were followed for up to 3 years. The resection rates after chemotherapy were calculated and the overall survival was estimated using the Kaplan–Meier method for Group 1 (G1, potentially resectable), Group 2 (G2, not resectable and tumor-related symptoms) and Group 3 (G3, not resectable and asymptomatic). RESULTS: Of 578 patients, 562 were classified into G1 (n = 165), G2 (n = 224) or G3 (n = 173). The resection rate of any site was higher in G1 (57.0%) than in G2 (11.2%) and G3 (11.6%). G1, G2 and G3 showed median overall survivals (95% confidence interval) of 45.9 (38.1–not available), 16.7 (14.5–18.8) and 30.6 (23.2–34.8) months, respectively (P < 0.0001). The common tumor-related symptoms in G2 were pain, fatigue and anorexia, from which 31.7, 22.2 and 14.8% of the patients suffered at baseline. CONCLUSIONS: The expected efficacy and safety of first-line cetuximab-containing chemotherapy were demonstrated in patients with metastatic colorectal cancer under clinical practice in Japan. REGISTERED CLINICAL TRIAL NUMBERS: UMIN000007275